A presença chinesa nos estados falidos africanos: um olhar sobre o investimento em areas de conflito - Licório, Grasiela de Oliveira (2011)
The Chinese presence in Africa over the past five years has ceased to be based on solidarity and took strategic international positioning characteristics. China has achieved an average 70 billion dollars per year (Huang, 2008) in trade negotiations with the African continent, including countries facing situations of civil unrest, such as Sudan and Nigeria. This interaction does not impose conditionalities, which allows China to always maintain advantageous relationships financially and politically, regardless of what is the current regime. The aim of this study is to analyze this new Chinese position on the African continent, seeking to understand the consequences of this approach for both sides and their connection with the deepening of the conflict